An Analysis On Factors Influencing The Students’ Writing Skill On The Second Semester Students Of Islamic Education Program Of Islamic University Of Kuantan Singingi - Mellio fatria (LEMBAGA PENELITIAN DAN PENGABDIAN MASYARAKAT (LPPM) UNIKS, 2021)
The objectives of this research are to find out what factors that influence the improvement of the students’ writing skill on the second semester students of Islamic Education program of Islamic University of Kuantan Singingi. This is a descriptive qualitative research. The participants of the research were the students of on Islamic Education students of Islamic University of Kuantan Singingi, which consisted of 33 students. The instruments of this research were observation, fieldnotes, and interviews. After analyzing the data, the researcher found that the factors that influenced the improvement of their writing skill involved materials, media, classroom activities, classroom management, teacher’s approach, creative thinking, students’ motivation, amount of practice, student’ prior knowledge, students’ interaction, and students’ perception.